(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The aim of this study — to identify how anthropometric measurements are connected with spine sagittal curves in schoolchildren. Anthropometric and sagittal body posture measurements were performed for 405 schoolchildren, age range 10—13 years. Such anthropometric measurements as body height, weight, fat mass and fat free mass were assessed. Degrees of thoracic kyphosis and lumbar lordosis as sagittal profile features were evaluated. According to the data analysis could be concluded, that coherence between anthropometric parameters and spine’s sagittal profile differs according to gender. The number of statistically significant connections between these two parameters’ groups was greater in boys. Anthropometric measurements had greater coherence with thoracic kyphosis in comparison with lumbar lordosis. Body weight and fat mass were statistically significantly different according to kyphosis and lordosis values in boys, although fat-free body mass had no significant difference with sagittal curves’ expression. Body weight, fat mass and fat-free body mass among girls were associated only with thoracic kyphosis. Keywords: thoracic kyphosis, lumbar lordosis, height, weight, fat mass.